New records of Van Rossem’s Gull-billed Tern (Gelochelidon nilotica vanrossemi) nests in the Coast of Jalisco, Mexico - Hernández-Vázquez, Salvador; Bojorques-Castro, Jesús; Almanza-Rodríguez, Humberto; Rodríguez-Torres, Daniela; Díaz-Pereyra, Dulce (Huitzil Revista Mexicana de Ornitología, 2015)
We report new nesting sites for the Van Rossem’s Gull-billed Tern (Gelochelidon nilotica vanrossemi) at the Agua Dulce and Xola-Paramán lagoons, in the coast of the state of Jalisco, Mexico. We first recorded the nests on 19 June, 2013 and monitored them at two-week intervals until 2 August, 2013. We found eight nests in the Agua Dulce lagoon and 16 in the Xola-Paramán lagoon. These new records expand the known nesting range of the Van Rossem’s Gull-billed Tern along the Pacific coast, from San Diego, California to the state of Colima in Mexico.